Childhood and adult socioeconomic position interact to predict health in mid life in a cohort of British women - Daniel Nettle; Melissa Bateson (PeerJ, 2017)
Background Low childhood socioeconomic position (cSEP) is associated with poorer adult health, even after adult socioeconomic position (aSEP) is adjusted for. However, whether cSEP and aSEP combine additively or non-additively in predicting adult health is less well studied. Some evidence suggests that the combination of low cSEP and low aSEP is associated with worse health than would be predicted from the sum of their individual effects. Methods Using data from female members of the British National Child Development Study cohort, we developed continuous quantitative measures of aSEP and cSEP, and used these to predict self-rated health at ages 23, 33, and 42. Results Lower aSEP predicted poorer heath at all ages. Lower cSEP predicted poorer health at all ages, even after adjustment for aSEP, but the direct effects of cSEP were substantially weaker than those of aSEP. At age 23, the effects of cSEP and aSEP were additive. At ages 33 and 42, cSEP and aSEP interacted, such that the effects of low aSEP on health were more negative if cSEP had also been low. Conclusions As women age, aSEP and cSEP may affect their health interactively. High cSEP, by providing a good start in life, may be partially protective against later negative impacts of low aSEP. We relate this to the extended ‘silver spoon’ principle recently documented in a non-human species.